2015
DOI: 10.1117/1.jbo.20.6.066011
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of over-the-counter vitamin supplement intake on urine fluorescence to optimize cancer detection by fluorescence cystoscopy

Abstract: Fluorescence cystoscopy (FC) efficiently enhances the detection and improves the therapeutic management of early bladder cancer. During an FC, about 150 ml of water is needed to inflate the bladder. The water is quickly diluted by urine which can be fluorescent. If this bladder washout fluid (BWF) becomes fluorescent, the FC images are frequently degraded. Unfortunately, it is unclear which elements of the diet may contribute to this background fluorescence. We propose to start this exploration with over-the-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In contrast, a peak at 470 ± 10 nm with varying intensities is clearly seen for all the urine samples. It is well established that the inherent fluorescence and color of the urine samples vary according to the dietary intake, body metabolism, pre-existing complications, and age. , Therefore, fluorometric and colorimetric assays are influenced by the inherent fluorescence of urine that may interfere with the assay responses, especially for the detection of less abundant biomarkers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In contrast, a peak at 470 ± 10 nm with varying intensities is clearly seen for all the urine samples. It is well established that the inherent fluorescence and color of the urine samples vary according to the dietary intake, body metabolism, pre-existing complications, and age. , Therefore, fluorometric and colorimetric assays are influenced by the inherent fluorescence of urine that may interfere with the assay responses, especially for the detection of less abundant biomarkers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…14 It has been shown that the metabolization of consumed over-the-counter (OTC) vitamin supplements showed the highest fluorescence values of the urine at 8−10 h after intake of the OTC. 15 Baseline levels were reached 24 h after intake. 15 According to that study, the OTC vitamin supplement generates fluorescence in urine, which might lead to a wrong interpretation of diagnostic results using fluorescence cystoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…15 Baseline levels were reached 24 h after intake. 15 According to that study, the OTC vitamin supplement generates fluorescence in urine, which might lead to a wrong interpretation of diagnostic results using fluorescence cystoscopy. Therefore, it was recommended to avoid vitamin supplements during the week performing a fluorescence cystoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Known compounds with altered fluorescence intensity observed in case of some cancers (bladder, breast, etc.) include free (unbound) NAD(P)H molecules, flavins, porphyrins, proteins and pigments [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%